Studi Eksegetis Yohanes 1:1-18 Sebagai Apologetik Terhadap Kristologi Saksi Yehuwa - Pangeran Manurung (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2016)
Eksegesa John 1 : 1-18 shows that the Jehovah's Witness teachings deviate from the truth of the Bible and dangerous for Christians . The danger Christology of Jehovah's Witnesses should be bringing us to the prudence and discretion to reject it . It can be said that Jehovah's Witnesses do not include Christianity in accordance with the search results against their teachings . first ; they do not recognize the Bible that has been issued by the Indonesian National Bible Institute and consider if the Bible has too much harm to use their own New Translation of the Holy Scriptures that have been proven not a translation , but just a collection of interpretations and teachings of their leader alone . second ; Jehovah's Witnesses do not acknowledge Jesus as Lord and Savior only . They simply believe that salvation is obtained through belief in Jehovah and his kingdom and perform service message and follow the trial associations . Before errors interfere Christology Christology of Jehovah's Witnesses Bible , please note that the topic of Christology is the difference between Christianity and other religions . This discussion has also become one of the topics that face many attacks from the outside or from within Christianity , either in the form of religion , philosophy , and ideology . The debate on this topic appeared since the beginning of Christianity , and give rise to a long and complex debate for nearly three centuries ( 300 years ) !! . Such debates will continue to exist throughout the period and just a rehash issues that had once appeared . And Christians should study the various debates and views of the ever emerging that are not easily fooled by the views back to this era .Eksegesa John 1 : 1-18 has been done and produce a biblical Christology and biblical correct . The truth is not in doubt because of the analysis conducted in accordance with the procedures and rules that apply in general . Now if Christology Christology of John compared with Jehovah's Witnesses, it will show a striking difference . Once observed , Christology Witnesses builds upon the interpretation of individuals who previously have had a negative Christological doctrine . Conclusion those who think that Jesus is the firstborn of Creation ; Jesus was a human being ; Jesus is God in creating a peer ; Jesus lower than God , Jesus is the Angel Gabriel , and other Christological doctrine which basically degrading nature of Christ is a form of insult to the majesty of Christ . The Bible clearly and emphatically teaches that Christ is God incarnate , private alpha and omega , the creator of all that exists , and the equivalent of God the Father . Summing Christ as superior human or clear eldest creation is false teachings . The followers of Jehovah's Witnesses must repent. Amen